Psychomotor Assessment in Teaching and Educational Research - Ilaria Viscione; Francesca D'Elia; Rodolfo Vastola; Maurizio Sibilio (Athens Institute for Education and Research, 2017)
The early identification of motor difficulties through psychomotor assessment is fundamental for the planning of individualized and differentiated educational programs. In the field of motor activity, observation plays a crucial role. This is characterized by the knowledge of the level of psychomotor and auxiological development, the definition of aims and methodology, and the allocation of timing required for observation. Therefore, psychomotor assessment not only measures performance, but it also analyzes an array of aspects linked to it in a multidisciplinary view. In this study, a qualitative assessment of the motor performance of 379 preschool children residing in the province of Salerno was carried out using the Movement ABC checklist. In particular, the data obtained from observations on the motor behavior of the child was analyzed, in reference to the relationship between the body and the environment for the first four sections. The results showed a discontinuity in relation to the linear progression in terms of difficulty of motor tasks, as presented in the checklist. This highlighted features of everyday life and classroom activity that could help in guiding teaching for the recovery, development and enhancement of psychomotor skills.